Unmanned aerial vehicles : breakthroughs in research and practice (Engineering Science Reference, an imprint of IGI Global, 2019)
"This book is a critical source of academic knowledge on the design, construction, and maintenance of drones, as well as their applications across all aspects of society. Highlighting a range of pertinent topics such as intelligent systems, artificial intelligence, and situation awareness"--